Transitional Justice: Tasks Local and Provincial Governments Can Undertake in Nepal - Mainali, Sujit (GS WOW: Wisdom of Worthy Research Journal, 2024)
The Government of Nepal (GoN) signed a Comprehensive Peace Accord (CPA) with the Communist Party of Nepal (CPN) Maoist in 2006, ending a decade-long armed communist insurgency. However, tasks concerning transitional justice (TJ) remain unfulfilled. Following the promulgation of the constitution in 2015, Nepal established a three-tier government system. To address Nepal’s TJ process in a holistic manner, this study identifies tasks that local and provincial governments can efficiently perform. The constitution, along with several acts, policies, and directives, has been reviewed to determine the scope of local and provincial governments in carrying out TJ-related activities. The review indicates that while both provincial and local governments have vital roles to play, the role of local governments could be more significant if they execute activities in close consultation and collaboration with the central and provincial governments, as well as other state organs.